MEMBANGUN KEPERCAYAAN BISNIS : ANALISIS PEMASARAN TIKTOK LIVE DALAM KERANGKA ETIKA BISNIS ISLAM - Sahira Azzahra; Fauziah Tiara Anggraini; Mivtahul Janati Rahmi Fajri; Erma Nuril Fajriah; Agustiawan Agustiawan (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The development of digital technology has transformed business marketing strategies, one of which isthrough the live streaming feature on TikTok. TikTok Live provides business owners with the opportunity tointeract directly with consumers, build trust, and drive real-time sales. However, in practice, variouschallenges arise regarding the implementation of Islamic business ethics. This study aims to analyze thealignment of TikTok Live marketing strategies with the principles of Islamic business ethics, namely tauhid(unity), equilibrium (balance), free will, responsibility, and ihsan (benevolence). Using a qualitativedescriptive method and a sociological-juridical approach, this study finds that many marketing practices onTikTok Live do not fully comply with Islamic business ethics, particularly in terms of transparency, honesty,and consumer responsibility. Some business owners still use manipulative marketing techniques, such ascreating false urgency and making exaggerated claims, which can mislead consumers. Therefore, furtherefforts are needed to raise awareness of Islamic business ethics in digital marketing so that businesses canoperate not only profitably but also based on Islamic values and bring benefits to society.